Remdesivir: a strategy to face the COVID-19 virus (International Seven Journal of Health Research, 2023)
In December 2019, a new type of coronavirus was found to have emerged and the World Health Organization declared a state of public health emergency. In view of this, Remdesivir has been identified in many countries as a possible candidate for the treatment of Sars-Cov-2. Given these assumptions, this paper aims to highlight the current evidence on the mechanism of action of this drug in cells infected with COVID-19 through a literature review. Remdesivir is defined as a nucleoside analog prodrug substituted with 10-cyano. Its main function is to inhibit viral replication by competing with endogenous nucleotides for viral RNA incorporation. In a randomized double-blind study, intravenous Remdesivir had no efficacy on time to clinical improvement, mortality, or time to viral clearance in patients with severe COVID-19. In another study patients who received Remdesivir had a 10-day faster recovery compared to those who received placebo. It is concluded that one study was able to satisfactorily demonstrate the use of Remdesivir in patients with COVID-19, as patients had a short recovery time compared to placebo. However, more studies are needed to prove the efficacy of the drug to combat coronavirus. DOI: 10.56238/isevjhv1n1-002